Talon Cusps in Mandibular Incisors: An Unusual Presentation in a Child Patient - Prasanna Kumar Rao; Shishir Ram Shetty; Rachana V. Prabhu; K.M. Veena; Laxmikanth Chatra; Prashanth Shenai (Tabriz University of Medical Sciences, 2011)
Talon cusp is a dental anomaly also known as an eagle's talon. It is an extra cusp on an anterior tooth which arises as a result of evagination on the surface of a crown before calcification has occurred. The exact etiology is unknown. The incidence of talon cusp is less than 6%. Commonly involved teeth are maxillary incisors, usually unilateral but in some instances bilateral. The classical radiographical feature of talon cusp is double teeth appearance. The anomaly has been reported to be unusual in the mandibular dentition. This article reports an unusual case of talon cusp of permanent mandibular central incisors.